Hidden Redistribution in Higher Education - Maria Perrotta Berlin (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2013)
Low income countries, and in particular countries in Sub-Saharan Africa, have invested huge resources over the last 40 years in financing higher (university level) education, compared with the number of students at that level and with the corresponding expenditures for lower levels of education. I propose and test an elite capture hypothesis: that expenditure in tertiary education is partly used as a tool for redistribution towards the elites close to the political leaders. I fi nd that this hypothesis can explain a substantial part of the within-country variation in expenditures levels.
Keywords: C81; H52; I22; O55; 330; higher education; public expenditures; inefficient redistribution; Sub-Saharan Africa